2012
DOI: 10.1164/rccm.201203-0448oc
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Mortality in Obstructive Sleep Apnea in the Elderly: Role of Long-Term Continuous Positive Airway Pressure Treatment

Abstract: Severe OSA not treated with CPAP is associated with cardiovascular death in the elderly, and adequate CPAP treatment may reduce this risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
142
0
11

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(170 citation statements)
references
References 42 publications
9
142
0
11
Order By: Relevance
“…The main risk factors are male gender, age progression, obesity and craniofacial structure, and in the latter two factors the genetic and ethnic constitution can play a determining role [5]. Both the soft tissue of the upper airway and craniofacial characteristics contribute synergistically to the collapse of the pharynx, the so-called "anatomical balance" [5][6][7][8][9][10]. In addition, other factors in the pathophysiology of OSAS have been blamed for pharyngeal collapse.…”
Section: Pathophysiology Of Osamentioning
confidence: 99%
See 1 more Smart Citation
“…The main risk factors are male gender, age progression, obesity and craniofacial structure, and in the latter two factors the genetic and ethnic constitution can play a determining role [5]. Both the soft tissue of the upper airway and craniofacial characteristics contribute synergistically to the collapse of the pharynx, the so-called "anatomical balance" [5][6][7][8][9][10]. In addition, other factors in the pathophysiology of OSAS have been blamed for pharyngeal collapse.…”
Section: Pathophysiology Of Osamentioning
confidence: 99%
“…It is associated with changes in mood, cognition, worsening of quality of life, impaired glucose metabolism and other cardiovascular diseases such as stroke, coronary artery disease, congestive heart failure and atrial fibrillation [5]. Observational studies point to a higher rate of cardiovascular morbidity and mortality in patients with severe and untreated OSAS [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The first-line treatment for patients presenting OSA is continuous positive airway pressure (CPAP) therapy [9], which significantly ameliorates symptoms as well as its cardiovascular consequences [10][11][12]. We previously showed that successful CPAP treatment improved daytime baroreflex sensitivity and nitric oxide production in patients with moderate to severe OSA, hence CPAP may reduce the risk of cardiovascular complications due to endothelial dysfunction or increased sympathetic activity [8].…”
Section: Introductionmentioning
confidence: 99%
“…When adherence is greater than 4 hours of nightly use, 46 to 83% of OSA patients were reported to be nonadherent to the treatment [13]. Increasing daily use of CPAP lowers blood pressure [10] and reduces the risk of incident stroke [11] and cardiovascular death [12]. Vascular endothelial dysfunction and structural vascular changes have been implicated as early mechanisms in the pathophysiology of hypertension and other forms of vascular disease [14].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of CPAP is directly related to treatment compliance [1][2][3]. Observational studies have shown a reduction in cardiovascular mortality risk in severe OSA patients treated with CPAP and adequate compliance [4][5][6]. A recent randomised controlled trial (RCT) showed a reduction in cardiovascular events (including hypertension incidence) in patients with adequate CPAP compliance [7].…”
mentioning
confidence: 99%